Perceived Organisational Support and Organisational Commitment among Oil and Gas Offshore Employees in Malaysia - Ridwan Mokhtar; Sylvia @ Nabila Azwa Ambad; Sharifah Nurafizah Syed Annuar; Nelson Lajuni (Macrothink Institute, 2020)
With the fast growth of business and rapid changes in the economic landscape, organisational commitment remains an important subject to be discussed in any part of an organisation. Thus, the present study examines the effects of perceived organisational support on organisational commitment among offshore employees in Malaysia. A study was conducted by distributing online questionnaire via Google Forms among offshore employees. A total of 246 completed responses were collected, and data collected were then analysed using PLS-SEM 3.3.2. The outcomes suggest that all dimensions of perceived organisational support have a significant relationship towards organisational commitment among offshore employees in Malaysia, except for supervisor support.